Peningkatan Aktivitas dan Hasil Belajar Matematika Siswa Kelas V pada Materi Kelipatan Persekutan Terkecil (KPK) dan Faktor Persekutuan Terbesar (FPB) melalui Pembelajaran Kooperatif Tipe Team Games Tournament (TGT) di SDN 3 Sukajawa Bandar Lampung - Rohelyati Rohelyati (Program Studi PGSD, Jurusan Ilmu Pendidikan, STKIP PGRI Bandar Lampung, 2021)
Based on the results of the reflections of class V teachers at SDN 3 Sukajawa, teachers more often use lecture and assignment methods. Teachers have not used innovative and creative approaches, methods, and learning models. This causes students to be less enthusiastic about learning mathematics. To improve this, the Team Games Tournamet (TGT) type cooperative learning model was chosen. This research is a classroom action research which consists of 2 cycles, each cycle consisting of 3 meetings. The research subjects were teachers (researchers) and fifth grade students of SDN 3 Sukajawa with a total of 36 students. Research colleagues were selected as observers. Data were collected using test and non-test techniques. Data analysis used quantitative and qualitative descriptive analysis. The results showed that the quality of learning mathematics material from KPK and FPB through the application of the Team Game Tournament (TGT) type of cooperative learning model in class V SDN 3 Sukajawa has increased. The suggestion from the researcher is that research on the Team Games Tournament (TGT) type of cooperative learning model should not stop here, but can be continued to future research to obtain more accurate results regarding the Team Games Tournament (TGT) type of cooperative learning model.